Involvement of adenosine signaling pathway in migraine pathophysiology: A systematic review of clinical studies. (July 2022) - Thuraiaiyah, Janu; Kokoti, Lili; Al-Karagholi, Mohammad Al-Mahdi; Ashina, Messoud
Objective: To systematically review clinical studies investigating the involvement of adenosine and its receptors in migraine pathophysiology. Background: Adenosine is a purinergic signaling molecule, clinically used in cardiac imaging during stress tests. Headache is a frequent adverse event after intravenous adenosine administration. Migraine headache relief is reported after intake of adenosine receptor antagonist, caffeine. These findings suggest a possible involvement of adenosine signaling in migraine pathophysiology and its potential as a drug target. Methods: A search through PubMed and EMBASE was undertaken for clinical studies investigating the role of adenosine and its receptors in migraine, published until September 2021. Results: A total of 2510 studies were screened by title and abstract. Of these, seven clinical studies were included. The main findings were that adenosine infusion induced headache, and plasma adenosine levels were elevated during ictal compared to interictal periods in migraine patients. Conclusion: The present systematic review emphasizes a potentially important role of adenosine signaling in migraine pathogenesis. Further randomized and placebo-controlled clinical investigations applying adenosine receptors modulators in migraine patients are needed to further understand the adenosine involvement in migraine.